RATIONAL DIAGNOSTIC METHODS AND ALGORITHMS FOR DETECTING KIDNEY DISEASES IN CHILDREN - A.E. Naushabaeva; K.A. Kabulbaev; A.L. Rumyantsev; V. Brocker; J. Ehrich (Педиатрическая фармакология)
This review summarises the basic and essential laboratory tools for identifying and differentiating renal diseases in children. Furthermore, it describes the limits of out-dated techniques and the potential of new diagnostic laboratory methods. Diagnostic algorithms are shown which, together with supplementary methods allow, firstly, the diagnosis of the location of renal damage levels; secondly, clarification of the etiology of the disease and, thirdly, the characterisation of the stage of the renal function disorder.Key words: kidney diseases, diagnostics, symptoms of renal damage, children.